Participatory Democracy: Between the Political Promise and the Cost of Citizenship - Caid, Youcef (Journal of Legal Studies and Researches, 2025)
Participatory democracy empowers citizens to play a direct role in decision-making, enhancing authority legitimacy. However, fulfilling this political promise comes at a cost, requiring citizen awareness, influence, and genuine governmental inclusion. Despite the challenges, it remains a tool for transparency, making its implementation a subject of ongoing debate.